1986
DOI: 10.1111/j.1475-6803.1986.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Penn Square, Problem Loans, and Insolvency Risk

Abstract: This paper investigates the influence of the failure of Penn Square Bank of Oklahoma City on stock prices within the banking industry. This influence is compared to the results of previous studies of the failures of Franklin National Bank of New York and United States National Bank of San Diego. While each of these earlier studies finds only a transitory impact on bank securities, this paper finds evidence of a structural change in the pricing mechanism for bank stocks after the Penn Square failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Among others, Benston (1973), Aharony, Jones, and Swary (1980), Aharony and Swary (1981), Smirlock (1984), and Lamy and Thompson (1986) employ similar methods. But two problems inhere in this approach (Unal, 1988).…”
Section: 1 1979 Event Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, Benston (1973), Aharony, Jones, and Swary (1980), Aharony and Swary (1981), Smirlock (1984), and Lamy and Thompson (1986) employ similar methods. But two problems inhere in this approach (Unal, 1988).…”
Section: 1 1979 Event Studiesmentioning
confidence: 99%
“…Despite these many and variegated events, Lamy and Thompson (1986) treat the Penn-Square crisis as the dominant event in this time interval, using the market model to estimate shifts in market risk and unsystematic risk for the t00 trading days preceding and 25 trading days following July 6, 1982. They find no significant shift in market risk between these periods, but a significant shift in unsystematic risk.…”
Section: Event Studiesmentioning
confidence: 99%
“…Studies on the impact of bank-specific negative announcements (Madura and McDaniel, 1989;Grammatikos and Saunders, 1990;Wetmore and Brick, 1991;Lamy and Thompson, 1986) suggest that such announcements adversely affect the stock returns of financial institutions (FIs). Such an adverse impact may go beyond the FIs, and contagiously affect others, whether they are in the same line of business or not (Swary, 1986;Lang and Stulz, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found evidence of contagion following the FNB failure, but no evidence that the contagion effects were 'pure'. Lamy and Thompson (1986) and Peavy and Hempel (1988) examine contagion effects caused by Penn Square's failure, with mixed results. Swary (1986) examines the Continental Illinois failure and finds evidence of significant contagion effects.…”
Section: Bank Failures and Contagion Effects: Theory And Empirical Evmentioning
confidence: 97%
“…Second, Kaufman (1994), Aharony and Swary (1983), Lamy and Thompson (1986), Gay et al (1991), Jayanti et al (1996), Peavy and Hempel (1988), Swary (1986), Wall and Peterson (1990) all fail to find strong evidence (or any evidence at all) of contagion effects. One possible explanation is that the bank failures considered in these studies may not have been of sufficient importance to cause a loss of public confidence in the banking system as a whole.…”
Section: Introductionmentioning
confidence: 92%